2016
DOI: 10.1590/0102-6720201600010008
|View full text |Cite
|
Sign up to set email alerts
|

Acute Apendicitis in Liver Transplant Recipients

Abstract: Background : Appendicitis is a common cause of emergency surgery that in the population undergoing organ transplantation presents a rare incidence due to late diagnosis and treatment. Aim : To report the occurrence of acute appendicitis in a cohort of liver transplant recipients. Methods : Retrospective analysis in a period of 12 years among 925 liver transplants, in witch five cases of acute appendicitis were encountered. Results : Appendicitis occurred between three and 46 months after liver transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 9 publications
(30 reference statements)
1
18
0
Order By: Relevance
“…8 Fonseca-Neto et al encountered five cases of acute appendicitis among 925 liver transplants over a 12-y period. 18 Soravia et al identified 12 patients among a cohort of 2091 renal allograft recipients who developed acute colonic complications. 19 A retrospective analysis by Ooms et al of 1564 kidney recipients demonstrated that 50 patients (3.2%) developed an incisional hernia.…”
Section: Discussionmentioning
confidence: 99%
“…8 Fonseca-Neto et al encountered five cases of acute appendicitis among 925 liver transplants over a 12-y period. 18 Soravia et al identified 12 patients among a cohort of 2091 renal allograft recipients who developed acute colonic complications. 19 A retrospective analysis by Ooms et al of 1564 kidney recipients demonstrated that 50 patients (3.2%) developed an incisional hernia.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of acute appendicitis in liver transplant recipients is 0.01–0.49%. [ 1 2 ] de’Angelis et al . [ 1 ] reported that only 2% of solid organ transplant patients experienced appendicitis, and the median time from transplantation to emergency surgery was 2.4 years (range: 0.1–20.0 years).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the patients had acute appendicitis in the early stage after OLT (POD 9 and POD 11), which is much earlier than previous reports. [ 1 2 ] However, the risk factors remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In liver transplanted patients, cumulative incidence of AA ranges from 0.09 to 0.54% [ 82 , 92 94 , 96 ] demonstrating the rarity of this pathology in LT. In a recent meta-analysis, AA accounted only for 2% of all emergency surgery in transplanted patients [ 97 ].…”
Section: Common Acute Abdominal Infections In Transplanted Patientsmentioning
confidence: 99%